PENINGKATAN KUALITAS PRODUK MEBEL MELALUI APLIKASI FINISHING BERNUANSA MARMER DAN GRANIT - Muchoyar, Imam; Ikhwanuddin, Ikhwanuddin (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The  aim  of  the  training   Ipteks  program   is to  upgrade  of  cracking painting finishing   skill for carpeter  so that they aschive product  variations  to enhances customer  interest.The  training   is executed   in  Bantul  District,  trainers  are  15 person. The training  is execute  one weeks  continuously,  with the instrucors  from PT Propan  Raya  Yogyakarta   and  FT  Yogyakarta   State  University.   Activity method  are  impel  of  working   and  producing  with  material:  (l)    finishing teory,  (2)  demonstration,    (3)  apppiication   of finishing   marble  and  granite nuanced at training  place,  and (5) application  of finishing   on their shops.The  result  are:  (1)  The  trainers  mastery  in  theory  and  practice   of finishing  marble  and granite,  (2)  There are able to material   for on their own production,  (3)   tere  able  to apply   for on their  own production,  and  (4) so that they can make product  variations  that sell in their own show rooms.Key words: marble, granite.furniture,   small-middle industry